GAMBARAN PENATALAKSANAAN PENYAKIT DEABETES MELITUS DIPOLI PENYAKIT DALAM RSUD PARIAMAN - -, Agustika Antoni (Menara Ilmu, 2018)
The implementation of Diabetes Mellitus therapy can normalize the activity of insulin andblood glucose level to reduce the complication caused by DM, the highest prevalence of DM inYogyakarta 2,6%, DKI Jakarta 2,5%, North Sulawesi 2,4%, East Kalimantan 2,3% and WestSumatera 1.3%. The research purpose is to know the description of DM disease managementin Polyclinic Pariaman HospitalThe type of this research is descriptive. This research was conducted at Polyclinic PariamanHospital, the research population was all patients of Diabetes Mellitus with 82 samples withaccidental sampling technique. The data were collected by questioner, then the data wasprocessed by computerization and then analyzed.The result of the research was the highest respondent's diet management in the high categorywhich is 61 people (74.4%), the physical exercise of the respondents was the lowest in the lowcategory of 43 people (52.4%), the most respondent in the high category was 63 people(76.8% ) and the treatment of most respondents in the high category that is 48 people (58.5%).It is desirable for patients to follow all the management processes of diet management as wellas treatment therapies that have been determined by the hospital, so that DM disease can becured.Keywords : Diabetes Mellitus, therapy, Disease